Upgrading work on on floor tiles (toilet) at building department JKR Negeri Kelantan / Che Mohamad Shafiq Aiman Che Othman - Che Othman, Che Mohamad Shafiq Aiman (Universiti Teknologi MARA UiTM,Perak, 2021)
The purpose of these assignment and internship is to gain experience of work in their course and also can understand the scope of work in their course when they work in the industry. After that, this internship also to get a feel for different industries and increase the confidence level of communicate. My internship place is at Jabatan Kerja Raya (Jkr) Negeri Kelantan. In this company I learn many things about construction for example the stage of construction. After that, the duration of the internship is 4 month from 11 October 2021 to 30 January 2022.